KARAKTERISTIK GAYA BAHASA OPINI DAN PERSUASI SISWA KELAS XII DI SMA NEGERI 1 KOTA BENGKULU DALAM MENYUSUN ARTIKEL ILMIAH POPULER BERBASIS ISU KEBIJAKAN PUBLIK - Fatimah, Siti; Yumarni, Asmara; Randi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the characteristics of opinion and persuasive language styles used by grade XII students of SMA Negeri 1 Kota Bengkulu in compiling popular scientific articles based on public policy issues. The public policies used as stimulus included school zoning, national curriculum, and educational digitalization. The research approach used was descriptive qualitative with content analysis method. The data corpus in this study was 36 popular scientific articles written by grade XII students. Data collection techniques used structured assignment, documentation, and in-depth interviews. The research instrument was a text analysis guide validated through theory and source triangulation. The results showed that the dominant opinion language style used by students was affirmation language style (pleonasm and alliteration) to strengthen arguments, and comparison language style (simile and metaphor) to simplify complex policy concepts. In the aspect of persuasive language style, students tend to use rationalization and identification techniques as the main strategy to influence readers. The inclusion of popular diction and argumentative conjunctions became the main identifiers in their popular scientific articles. Although in general students were able to demonstrate critical thinking towards public issues, weaknesses were still found in the consistency of the application of Ejaan Yang Disempurnakan (EYD) V, especially in the writing of loanwords and correlative punctuation. This study implies the need for a more contextual exposition-argumentative writing learning model at the senior high school level.